The fictions of Arthur Cravan : poetry, boxing and revolution - Jones, Dafydd W. (Manchester University Press, 2019)
The legendary poet and boxer Arthur Cravan, a fleeting figure on the periphery of early twentieth-century European avant-gardism, is frequently invoked as proto-Dada and Surrealist exemplar. Yet he remains an insubstantial phenomenon, not seen since 1918, lost through historical interstices, clouded in drifting untruths. This study processes philosophical positions into a practical recovery - from nineteenth-century Nietzsche to twentieth-century Deleuze - with thoughts on subjectivity, metaphor, representation and multiplicity. From fresh readings and new approaches - of Cravan's first published work as a manifesto of simulation; of contributors to his Paris review Maintenant as impostures for the Delaunays; and of the conjuring of Cravan in Picabia's elegiac film Entr'acte - The fictions of Arthur Cravan concludes with the absent poet-boxer's eventual casting off into a Surrealist legacy, and his becoming what metaphor is: a means to represent the world.